Cyber-boom or cyber-bubble? (Economist, 2015)
The article looks at the Internet- and computer-security software industry in Israel, reporting on the growth of the industry and its exports and citing cybersecurity companies including CheckPoint and CyberArk. Topics include trends in the volume of Israel's weapons exports and the many Israelis who are trained in cyber-security skills while serving in the Israel Defence Forces (IDF).